Monitoring and Evaluation of School Principals Based on ICT (MOME’ATIK) in Optimizing Data-Based Planning at SDN No. 11 Kota Barat - Marsella Desriyarini Gui; Syaiful oktavianto H. Musa (Edumaspul: Jurnal Pendidikan, 2026)
ICT-Based Principal Monitoring and Evaluation (MOME’ATIK) is an innovative approach that aims to improve the effectiveness of educational planning at SDN No. 11 Kota Barat. Through the use of Information and Communication Technology (ICT), this program is designed to optimize the collection, analysis, and use of data in the decision-making process at the school level. In the digital era, the use of accurate and relevant data is very important for formulating appropriate policies. MOME’ATIK allows principals to monitor student academic development, teacher performance, and the effectiveness of learning programs in real-time. With this system, the data collected can be used to identify strengths and weaknesses in the implementation of educational programs, so that data-based planning can be carried out better. The results of the implementation of MOME’ATIK at SDN No. 11 showed an increase in teacher and student participation, as well as improvements in student learning outcomes. With integrated data-based reports, principals can take more appropriate and targeted strategic steps. This program not only supports improving the quality of education, but also encourages a culture of transparency and accountability in school management. Overall, MOME’ATIK has the potential to be a model that can be adopted by other schools to optimize data-based educational planning, with the hope of improving the quality of learning at the elementary level.